Implementation of Web Technology for Tourism and Creative Industry Data Collection - Wahdiniwaty, Rahma; Setiawan, Eko Budi; Wahab, Deden A (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This research to provide a system that can facilitate data collection on tourism and creative industries. This research uses a web-based application by utilizing geolocation technology from the google application programming interface. The method implemented in this research uses the software development life cycle waterfall model. The results obtained are that this web-based application can be used online to collect data on creative and tourism industries up to the latitude and longitude coordinates data stored in the database. The data used comes from the Greater Bandung area. The test results obtained a value of 100% of each item. The research results can impact the industrial and tourism sector, especially the stakeholders of related government agencies, so that they can support the acceleration of development, especially in the Greater Bandung area.